V.l.n.r.: Hylkema, Bommer, Van Lienden, Thomassen en Kaper. Demonstratieve bijeenkomst in de Veemarkthallen
V.l.n.r.: Hylkema, Bommer, Van Lienden, Thomassen en Kaper. Demonstratieve bijeenkomst in de Veemarkthallen.